Prevalence Pattern of Extended Spectrum Beta Lactamase Producing Escherichia coli in Beef in Traditional Markets: Pola Prevalensi Escherichia coli Penghasil Extended Spectrum Beta Lactamase pada Daging Sapi di Pasar Tradisional - Puput Ayu Novitasari; Kuntaman Kuntaman; Akhmad Sudibja; Jesyca Isabel Anggraini; Tri Anisa Istiqomah (Academia Open, 2026)
Background: Antimicrobial resistance represents a growing global health concern, with foodborne bacteria acting as important reservoirs in the transmission pathway. Specific background: Escherichia coli capable of producing Extended Spectrum Beta Lactamase has been frequently detected in animal-derived foods, particularly beef sold in traditional markets where sanitation practices are often inadequate. Knowledge gap: Despite numerous studies on livestock and slaughterhouses, evidence describing the prevalence pattern of Extended Spectrum Beta Lactamase producing Escherichia coli in beef at the traditional market level remains limited, especially in Surabaya. Aims: This study aimed to describe the prevalence pattern of Extended Spectrum Beta Lactamase producing Escherichia coli in beef sold in traditional markets. Results: A descriptive cross-sectional study was conducted on fifty beef samples collected from multiple vendors. Identification using MacConkey agar and confirmation with the Double Disk Synergy Test showed that 29 samples (58%) were positive for Extended Spectrum Beta Lactamase producing Escherichia coli, with variation across vendors. Novelty: This study provides direct phenotypic confirmation of Extended Spectrum Beta Lactamase producing Escherichia coli in beef from traditional market settings. Implications: The findings emphasize the need for routine microbiological monitoring and improved hygiene practices in traditional meat distribution to support food safety and public health protection. Highlights Extended Spectrum Beta Lactamase producing Escherichia coli detected in more than half of beef samples Prevalence pattern varied among traditional market vendors Traditional market meat handling presents substantial food safety challenges Keywords Beef, Escherichia Coli, Extended Spectrum Beta Lactamase, Traditional Markets, Antimicrobial Resistance